Understanding Purchase Decisions in Indonesian Social Commerce: The Effects of Social Proof, Perceived Scarcity, Perceived Value, and Parasocial Interaction through the Stimulus–Organism–Response Perspective - Lean Sahda Hafiza; Ratna Listiana Dewanti (International Journal of Management Science and Information Technology, 2026)
The rapid growth of social commerce has transformed consumer purchasing behavior, making it essential to understand the factors that influence purchase decisions in digital environments. This study aims to examine the effects of social proof, perceived scarcity, perceived value, and parasocial interaction on purchase decisions in social commerce in Indonesia. A quantitative research approach with a survey method was employed. Data were collected through an online questionnaire distributed to 100 social commerce users in Indonesia aged 20–35 years, selected using purposive sampling. The research instrument was tested for validity and reliability, and the data were analyzed using multiple linear regression with SPSS Statistics 25 for Windows. The results indicate that social proof, perceived scarcity, perceived value, and parasocial interaction simultaneously have a significant effect on purchase decisions. Partially, all four variables were found to have positive and significant effects on purchase decisions. Among the examined variables, perceived scarcity showed the strongest influence, followed by parasocial interaction, social proof, and perceived value. Furthermore, the coefficient of determination indicates that these variables explain 33.2% of the variance in purchase decisions, while the remaining 66.8% is influenced by other factors outside the research model. These findings contribute to the social commerce literature by highlighting the importance of social, psychological, and value-related factors in shaping consumer purchase decisions. The results also provide practical implications for businesses in developing effective digital marketing strategies to enhance consumer engagement and purchasing behavior.